Lens ray diagrams with a spreadsheet. (19th February 2018) - González, Manuel I
Abstract: Physicists create spreadsheets customarily to carry out numerical calculations and to display their results in a meaningful, nice-looking way. Spreadsheets can also be used to display a vivid geometrical model of a physical system. This statement is illustrated with an example taken from geometrical optics: images formed by a thin lens. A careful mixture of standard Excel functions allows to display a realistic automated ray diagram. The suggested spreadsheet is intended as an auxiliary didactic tool for instructors who wish to teach their students to create their own ray diagrams.